Physical Exercise Improves Peripheral BDNF Levels and Cognitive Functions in Mild Cognitive Impairment Elderly with Different BDNF Val66Met Genotypes - Crispim Nascimento, Carla Manuela [UNESP]; Pereira, Jessica Rodrigues [UNESP]; Andrade, Larissa Pires de [UNESP]; Garuffi, Marcelo [UNESP]; Ayan, Carlos; Kerr, Daniel Shikanai; Talib, Leda Leme; Cominetti, Marcia Regina; Stella, Florindo [UNESP] (Ios Press, 2015)
The benefits of physical exercise on improvements in brain-derived neurotrophic factor (BDNF) levels and cognitive functioning have been reported in the literature. However, the variability of individual responses may be linked to genetic differences. BDNF is considered one of the most plausible factors involved in the cognitive benefits associated with physical activity practice. A single nucleotide polymorphism localized in the gene that codes BDNF results in a missense mutation that promotes an amino acid substitution (Val66Met) in the protein. This process has been associated with decreased levels of BDNF secretion, with corresponding impairments in specific cognitive functions. Therefore, the objective of this study was to analyze the effects of a multimodal physical exercise program on peripheral BDNF levels and cognitive functions in elderly individuals with mild cognitive impairment (MCI). The participants were genotyped for the BDNF Val66Met polymorphism. Cognitive functions were assessed by the Montreal Cognitive Assessment (MoCA) prior to and after the intervention. Forty-five participants were assigned to the control and trained groups. The trained group participated in a multimodal physical training for a 16-week period. The results showed a significant between-subjects interaction (p < 0.05), which indicates the beneficial contribution of training on cognitive functions independent of the BDNF genotype. However, only participants with BDNF-Met genotypes exhibited significant improvements in peripheral BDNF levels. The BDNF genotype appears to modulate the effects of physical exercise on BDNF secretion, but it does not influence cognition. This is the first study that evaluated the influence of a BDNF polymorphism on physical activity and cognition performance in elderly MCI individuals.
Keywords: Brain-derived neurotrophic factor; cognition; genetic polymorphism; mild cognitive impairment; physical exercises